IMPLEMENTASI PEMBELAJARAN KONTEKSTUAL BUDAYA LITERASI MEMBACA DALAM MENINGKATKAN MUTU DIMENSI PROFIL LULUSAN DI SEKOLAH DASAR. - Ade Tutti Rokhayati Rosa; Santi Susilawati Suherman; Rahayu AD Putra Aulia; Piki Ramdhani Askar; Bambang Syaf Rizal (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
In essence, reading is an important part of literacy, considering that elementary school students are required to have basic reading skills. Learning activities are inseparable from reading knowledge and comprehension. Given the importance of elementary school students' reading skills, teachers need to stimulate students' interest and motivation to read through contextual literacy habits. Furthermore, teachers should also participate in various literacy webinars to identify various media and literacy learning models that suit the characteristics of elementary school students, such as the CTL (Contextual Teaching and Learning) learning model used in this study. The general objective of this research is to determine the implementation of contextual learning of reading literacy culture in realizing the graduate profile dimension. The specific objectives of this study are to obtain an overview/information and analyze the planning, organization, implementation, and evaluation of the implementation of contextual learning of reading literacy culture in improving the quality of the graduate profile dimension in elementary schools. The research method used was qualitative, utilizing interviews and observations. Based on the research results, it can be concluded that the implementation of contextual learning for reading literacy culture can improve the quality of graduate profiles in educational units.